The Relationship Between Diet and Stress with the Incidence of Hypertension in Pregnant Women in the Caile Health Center Work Area - Nabila; Sri Eka Juniarly; Mitra Asriani Amin (Jurnal Life Birth, 2022)
Hypertension in pregnancy is an increase in blood pressure where the systole pressure is 140 mmHg or diastole pressure is 90 mmHg, and the increase in systolic pressure is 15 mmHg compared to blood pressure before pregnancy. This study aims to determine the relationship between diet and stress with the incidence of hypertension in pregnant women in the Caile Health Center Working Area, Bulukumba Regency. The type of research used is an analytical observational study with a cross-sectional design. The samples in this study were all pregnant women who had hypertension and did not have hypertension totaling 59 people. The data collection instrument is in the form of a questionnaire on the diet and stress of pregnant women. data were analyzed using Chi-square. The results of this study show that most of the diets of pregnant women in the Caile Health Center, Bulukumba Regency, are in the unhealthy category. Most of the stress levels of pregnant women at the Caile Health Center are moderate. There is a relationship between diet and the occurrence of hypertension in pregnant women in the work area of the Caile Health Center (p = 0.001; α = 0.05). There was no relationship between stress and the incidence of hypertension in pregnant women in the work area of the Caile Health Center (p = 0.167; α = 0.05). There is a relationship between diet and no relationship between stress and the incidence of hypertension in pregnant women in the Caile Health Center Working Area, Bulukumba Regency in 2020